Dynamic changes of fecal microbiota in a weight-change model of Bama minipigs - Zeng, Bo; Chen, Li; Kong, Fanli; Zhang, Chengcheng; Chen, Long; Qi, Xu; Chai, Jin; Jin, Long; Li, Mingzhou (Frontiers in Microbiology, 2023)
Obesity is closely related to gut microbiota, however, the dynamic change of microbial diversity and composition during the occurrence and development process of obesity is not clear. A weight-change model of adult Bama pig (2 years) was established, and weight gain and weight loss treatments were implemented, with corresponding analyses of fecal microbiota changes. During the weight gain period (1~27 week), the alpha diversity of fecal microbiota exhibited a "down-up-down" fluctuations, initially decreasing, recovering in the mid-term, and decreasing again in the later stage.Beta diversity also significantly changed over time, indicating a gradual deviation of the microbiota composition from the initial time point. Bacteroides, Clostridium sensu stricto 1, and Escherichia-Shigella showed positive correlations with weight gain, while Streptococcus, Oscillospira, and Prevotellaceae UCG-001 exhibited negative correlations. In the weight loss period (30~38 week), the alpha diversity further decreased, and the composition structure underwent significant changes compared to the weight gain period. Christensenellaceae R-7 group demonstrated a significant increase during weight loss and showed a negative correlation with body weight. Porphyromonas and Campylobacter were positively correlated with weight loss. Both long-term fattening and weight loss induced by starvation led to substantial alterations in porcine gut microbiota, and the microbiota changes observed during weight gain could not be recovered during weight loss. This work provides valuable resources for both obesity-related research of human and microbiota of pigs.